Transformative impacts in the existing curriculum : A study of developing learner agency and broadening career horizons - López-Íñiguez, Guadalupe; Bennett, Dawn (ISME, 2022)
Establishing a career as a performing classical musician is strongly linked to 1) facing fierce competition during and after professional studies, 2) the ability of developing a multiplicity of skills that go beyond the craft of the instrument/voice, and 3) being flexible/agile to adapt to the constant changes and demands of the music industry. However, music majors seem to realize this towards the end of their studies in higher music education. This leads to an enormous pressure to become employable when they graduate, leaving many to depend on luck and stressful learning on-the-job situations. Considering this situation, higher music education is under political scrutiny, as it should not only produce graduates, but employable ones – thus, maximising revenue generation. This asks for curricular transformations that have the potential to support music students in becoming agentic and embracing a learner identity – that is being artistically and professionally autonomous, and ready to embrace lifelong learning as an exciting part of their careers. This paper presents a socio-constructivist intervention to broaden career horizons and develop the much-required learner agency in 7 classical music majors. Authentic and scaffolded strategies related to employability in the music industry, relevant lectures and seminars of increasing difficulty, as well as a panel discussion with international musicians was offered to all participants as part of their studies during a semester-long class. Preliminary results indicated certain areas for improvement common to all participants such as social interaction and communication skills, variety within and beyond performance roles, and occupational and emotional literacy. Taking that into consideration, resources on critical reflection and career planning were further developed during the study. This supported the participants in embracing a positive attitude to learning, a more inclusive view of career pathways and musical identities, and an openness to discussing concerns with colleagues—all aspects related to musicians’ learner identity.
Keywords: musiikki; musiikkikasvatus; urakehitys; muusikot; urasuunnittelu